2014
DOI: 10.1016/j.cell.2014.03.048
|View full text |Cite
|
Sign up to set email alerts
|

RECQL5 Controls Transcript Elongation and Suppresses Genome Instability Associated with Transcription Stress

Abstract: SummaryRECQL5 is the sole member of the RECQ family of helicases associated with RNA polymerase II (RNAPII). We now show that RECQL5 is a general elongation factor that is important for preserving genome stability during transcription. Depletion or overexpression of RECQL5 results in corresponding shifts in the genome-wide RNAPII density profile. Elongation is particularly affected, with RECQL5 depletion causing a striking increase in the average rate, concurrent with increased stalling, pausing, arrest, and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
186
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(204 citation statements)
references
References 47 publications
18
186
0
Order By: Relevance
“…RECQL5 has a well-established role in maintaining genomic stability (Aygun and Svejstrup 2010;Saponaro et al 2014). While the mechanistic relevance of MLL2-RECQL5 interaction is yet to be investigated, the connection spurred us to investigate the potential role of MLL2 in the maintenance of genome integrity.…”
Section: Mouse Cells Defective For Mll2 Present Genomic Instabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…RECQL5 has a well-established role in maintaining genomic stability (Aygun and Svejstrup 2010;Saponaro et al 2014). While the mechanistic relevance of MLL2-RECQL5 interaction is yet to be investigated, the connection spurred us to investigate the potential role of MLL2 in the maintenance of genome integrity.…”
Section: Mouse Cells Defective For Mll2 Present Genomic Instabilitymentioning
confidence: 99%
“…We recently reported that RECQL5, a member of the RECQ family of helicases, is a general RNA polymerase II (RNAPII) elongation factor that is important for preserving genomic stability during transcription (Saponaro et al 2014). Indeed, depletion of RECQL5 results in increased pausing, stalling, arrest, and/or backtracking (collectively referred to as transcription stress) at sites that overlap with regions of genome instability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…RECQ5 prevents transcription-associated DSBs by suppressing RNAPII-dependent transcription initiation 18 , and this may be achieved by the interaction between RNAPII and the RECQ5 KIX domain, which blocks the binding of transcription elongation factor TFIIS to RNAPII 19 . RECQ5 is also known to interact with the active RNAPII (RNAPIIo) elongation complex to maintain the transcription elongation rate and prevent genome instability 15,20,21 . However, the exact mechanism by which RECQ5 maintains genome stability during transcription elongation has also not been determined.…”
mentioning
confidence: 99%
“…A recent paper has shown that RECQL5 slows down RNA polymerase II elongation and increases the robustness of transcription. Depletion of RECQL5 increases polymerase pausing and leads to genomic instability with gains and losses in common fragile sites and long genes, further supporting that stalled forks, regardless of the cause, can ultimately derive into pro-tumoral mutations [58]. These data suggest that RECQL5 may be limiting the generation of R-loops, yet further analyses should address this point.…”
Section: Rs As a Fuel Of Tumorogenesismentioning
confidence: 86%